Clinical Evaluation of Medical Devices Principles and Case Studies - Becker, Karen M.; Whyte, John J. (Humana Press : Imprint: Humana, 2006)
Highly praised in its first edition, Clinical Evaluation of Medical Devices: Principles and Case Studies, Second Edition has been expanded and updated to include the many innovations and clinical research methods that have developed since the first edition, as well as current information on the regulatory, legal, and reimbursement environment for medical devices. The book's deeply experienced authors summarize the key principles and approaches employed in medical device clinical trials and illustrate their uses in a revealing series of detailed, real-world case studies. Highlights include new information on the requirements and process for gaining reimbursement from Medicare and private insurers on new products-including case studies of research specifically designed for this purpose-and new statistical methods applied to medical device trials. Additional case studies provide examples of combination products, three-phase development models (i.e., feasibility, FDA approval, and Medicare reimbursement), and novel study designs. The cases demonstrate a wide range of designs that have been successfully applied to many different research problems, as well as to a variety of therapeutic or diagnostic products. Authoritative and highly practical, Clinical Evaluation of Medical Devices: Principles and Case Studies, Second Edition, provides a gold-standard resource for clinical professionals and regulatory specialists working at the forefront of new therapeutics, diagnostics, and medical device development and marketing today.